2017
DOI: 10.1371/journal.pone.0172714
|View full text |Cite
|
Sign up to set email alerts
|

Effector-independent reduction in choice reaction time following bi-hemispheric transcranial direct current stimulation over motor cortex

Abstract: Increased reaction times (RT) during choice-RT tasks stem from a requirement for additional processing as well as reduced motor-specific preparatory activation. Transcranial direct current stimulation (tDCS) can modulate primary motor cortex excitability, increasing (anodal stimulation) or decreasing (cathodal stimulation) excitability in underlying cortical tissue. The present study investigated whether lateralized differences in choice-RT would result from the concurrent modulation of left and right motor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
1
17
1
1
Order By: Relevance
“…The results of the present study are in principle accordance with those of others, which showed an impact of tDCS on RT tasks. For example, when RT was evaluated before and after 10 min of tDCS application, faster RTs were found after stimulation (Drummond et al, 2017). Other studies showed a similar impact of tDCS on motor performance in RT tasks (Müller et al, 2008;Nitsche, Schauenburg, et al, 2003).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The results of the present study are in principle accordance with those of others, which showed an impact of tDCS on RT tasks. For example, when RT was evaluated before and after 10 min of tDCS application, faster RTs were found after stimulation (Drummond et al, 2017). Other studies showed a similar impact of tDCS on motor performance in RT tasks (Müller et al, 2008;Nitsche, Schauenburg, et al, 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Sixty right-handed volunteers, 31 women and 29 men (mean age = 25.9 ± 3.03 years), participated in the study. Sample size was determined based on previous studies about the effect of tDCS on RT tasks (Drummond et al, 2017;Verissimo, Barradas, Santos, Miranda, & Ferreira, 2016). All subjects were healthy and without evidence of neurological or psychiatric disorders, and none of them was under central nervous system active medication.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). In addition, bi-hemispheric montages are at least as effective as uni-hemispheric ones [19][20][21] or can even improve the effects on task performance [22][23][24]. Secondly, we reduced the current amplitude from 2mA to 1mA and the duration of stimulation from 20 minutes to 13 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single tDCS session has been shown to increase motor performance or skill learning (Nitsche et al, 2003b;Vollmann et al, 2013;Ammann et al, 2016;Kaminski et al, 2016;Jackson et al, 2019;Kumari et al, 2019). tDCS-induced performance enhancement has not only been described for simple motor tasks such as tapping (Saimpont et al, 2016) and reaction time tasks (Nitsche et al, 2003b;Drummond et al, 2017;Hupfeld et al, 2017), but also for complex whole-body tasks such as balancing (Dutta et al, 2014;Kaminski et al, 2016). Moreover, further studies demonstrated that tDCS is capable of increasing endurance performance during cycling (Okano et al, 2015;Vitor-Costa et al, 2015;Angius et al, 2018a;Park et al, 2019) and running (Park et al, 2019) as well as leg muscle power (Tanaka et al, 2009).…”
Section: Performance Enhancement Using Non-invasive Brain Stimulationmentioning
confidence: 99%